MEDIA LUAR RUANG SERTA DAMPAKNYA TERHADAP KUALITAS DAN LINGKUNGAN HIDUP MASYARAKAT - Pramesti Saniscara (Jurnal Dimensi DKV Seni Rupa dan Desain, 2022)
Outdoor Media and Its Impact on People and Environmental Quality. In the rapidly developing world, the development of the field of advertising has also experienced significant progress. This development is shown through the number of advertisements that appear around our everyday living space. Starting from television, newspapers, magazines, radio, billboards, and videotron to running ads that are affixed to private and public transport. All of these media aim to attract as much public attention as possible to increase the sales of products/services advertised, also, as much as possible. But often the installation of this advertising media is not accompanied by a thorough consideration of the influence on the quality of life of the society and the surrounding environments. Taxes that tend to be affordable, and government regulations that is excluding the quality of the environment where billboards can be installed can cause people to be exposed to ‘sampah visual’ or visual waste from many advertisements that are not necessarily needed. Media Luar Ruang Serta Dampaknya Terhadap Kualitas dan Lingkungan Hidup Masyarakat. Dalam perkembangan dunia yang makin pesat, perkembangan dunia periklanan juga mengalami kemajuan yang signifikan. Perkembangan ini ditunjukkan melalui banyaknya iklan yang muncul di sekitar ruang hidup manusia. Mulai dari televisi, koran, majalah, radio, papan reklame, videotron hingga iklan berjalan yang ditempelkan pada kendaraan pribadi beberapa orang. Semua media ini bertujuan untuk menarik perhatian masyarakat sebanyak-banyaknya sehingga dapat meningkatkan penjualan produk/jasa yang diiklankan sebanyak-banyaknya juga. Namun seringkali pemasangan media iklan ini tidak diimbangi dengan pertimbangan yang menyeluruh akan dampaknya terhadap kualitas hidup masyarakat dan lingkungan hidup sekitarnya. Pengenaan pajak yang cenderung murah, dan regulasi pemerintah yang kurang mempertimbangkan kualitas lingkungan tempat pemasangan papan reklame bisa mengakibatkan masyarakat terpapar sampah visual dari banyaknya iklan yang belum tentu dibutuhkan.